Typology of historical baths of Kermanshah with emphasis on the location - amin ghahramani tolabi; sayed ali nouri (تحقیقات کاربردی علوم جغرافیایی)
Baths are among the public buildings whose shape and architecture have changed during different historical periods. Due to the importance of these valuable buildings. Kermanshah is one of the cities that during the historical period, especially in the Qajar period, due to its location on the path of Atbat-e-Aliat, was considered by the rulers of the time and has many textures and examples of historical baths. Therefore, the present study seeks to identify the types of historical baths in Kermanshah province with emphasis on the location. To achieve this, it is necessary to study the factors affecting the formation, location in urban, rural and neighborhood contexts, spatial geometry of Kermanshah baths. The research method in this research is a descriptive-analytical method based on field studies, analysis of the location, structure, architecture, decorations, proportions and materials of 12 samples of baths in Kermanshah province and a comparative-historical study of the samples. The results of this study show that Kermanshah province baths in terms of location are divided into 6 types: baths in the bazaar, single baths in neighborhoods, twin baths in neighborhoods, baths as an element of a complex in neighborhoods, baths in houses and baths They are divided in the rural context. The geometry of Kermanshah bath spaces is a function of the location in the city or village. Communication spaces and corridors in neighborhood and market-affiliated baths are based on the big measure, but in private baths and in-house baths and rural baths are based on the small measure. The main spaces of urban baths are decorated with limestone, but rural baths do not have limestone decorations. All the baths studied have 3 main spaces: Bine, garmkhaneh and khazineh, and the area of ​​the garmkhaneh space is relatively larger and larger than Bine, space.